Marine Litter Management Policy: State Responsibilities And The Role Of Local Wisdom - Ai Permanasari; Sirait, Yohanes Hermanto (Jurnal Mulawarman Law Review, 2020)
Indonesia as the biggest maritime state has not only advantages but also obstacles in managing sea. Called potential because of its large resources but it also brings into a fact of the lack in exploitation of the sea. Such transportation and exploitation have caused a lot debris in the sea which is harmful. This article aims to examine state responsibility in prevent and tackle marine debris. It also aims to enhance local wisdom as solution. This article is normative juridical, using statute and conceptual approach. It is made deductive from specific issue into general issue based on primary, secondary, and tertiary legal materials. After collecting all material, this article then analyzes it qualitatively. The result show that state responsibility has been implemented only in level of regulation. Although some regulation has underlined local wisdom as important matter, in fact, Indonesia still in process of inventory related local wisdom and still far from enhancing the local wisdom as solution to prevent and tackle marine debris. These practices are different to some states which apply their local wisdom as one of solution. Therefore, Indonesia must collaborate legal policy and local wisdom to achieve higher result in preventing and tackling marine littering. A legal policy that born from the way of life in community may accepted better.